2007
DOI: 10.1002/jcc.20601
|View full text |Cite
|
Sign up to set email alerts
|

Generation of basis sets with high degree of fulfillment of the Hellmann‐Feynman theorem

Abstract: A direct relationship is established between the degree of fulfillment of the Hellman-Feynman (electrostatic) theorem, measured as the difference between energy derivatives and electrostatic forces, and the stability of the basis set, measured from the indices that characterize the distance of the space generated by the basis functions to the space of their derivatives with respect to the nuclear coordinates. On the basis of this relationship, a criterion for obtaining basis sets of moderate size with a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[80] An advantage for using machine learning models to do this is that long-range forces calculated from densitybased machine learning models converge much quicker with respect to training cluster size compared to forcebased models. [25] While the aug-cc-pvdz basis set used to train the model in this work is not large enough to fulfill the requirements for accurate Hellmann-Feynman forces, [81,82] the accuracy of the machine learning electron densities suggests that with more complete basis sets the model could be directly applied for ab initio molecular dynamics.…”
Section: Additional Applications For the Machine Learning Modelmentioning
confidence: 99%
“…[80] An advantage for using machine learning models to do this is that long-range forces calculated from densitybased machine learning models converge much quicker with respect to training cluster size compared to forcebased models. [25] While the aug-cc-pvdz basis set used to train the model in this work is not large enough to fulfill the requirements for accurate Hellmann-Feynman forces, [81,82] the accuracy of the machine learning electron densities suggests that with more complete basis sets the model could be directly applied for ab initio molecular dynamics.…”
Section: Additional Applications For the Machine Learning Modelmentioning
confidence: 99%
“…We follow the strategy of Rico et al [25] in constructing the HF optimized basis sets. This approach relies on the observation that the Pulay force can be reduced with a basis that accurately reproduces its own spatial derivatives with respect to nuclear coordinates [29,30].…”
Section: Hellmann-feynman Optimized Basis Setmentioning
confidence: 99%
“…Pioneering work by Rico et al [25] has demonstrated that specially optimized basis sets can suppress the Pulay force. In their proof of principle work, Rico et al showed that atom-centered Slater-type orbital basis sets constructed to be flexible enough to describe the derivative of the wave function |∂Ψ/∂ R I afford noticeably attenuated Pulay forces.…”
Section: Introductionmentioning
confidence: 99%
“…As remarked in the introduction, integrals of the first type are needed for the calculation of derivatives [11] of the electron energy and density, as well as for the analysis of the basis set stability [10]. An example of these integrals is reported in Table I.…”
Section: Computational Testsmentioning
confidence: 99%
“…Though particular expressions for these conventional integrals are known from other procedures, the present method has the advantage of giving their master formula, which enables to obtain nonconventional integrals such as multipolar moments associated to fragments of two-center charge distributions or overlap integrals containing derivatives of STO. The former is useful for computing atomic multipoles, electrostatic potentials of molecules, or molecular interactions [9], and the latter, in the study of basis sets stability [10], and in the calculation of the derivatives of electronic energy [11], nonadiabatic coupling matrix elements [12], and so forth.…”
Section: Introduction Imentioning
confidence: 99%